Knowledge Management - Kransdorff, Arnold (Business Expert Press, 2009)
Ebook from IG Library ; Conceived just 15 years ago, knowledge management (KM) is the business discipline about which managers perhaps know the least. Having spent pots of money investing in it, the benefits ts are still marginal. That is because practitioners are still feeling their way. Now that the boom days are temporarily over, it is perhaps timely that KM can be more fully exploited, for it conceals an application that is indispensable for the foreseeable struggle ahead. Recessions conventionally mean drawing in one's horns. But what if there was another way through the minefield? The neglected KM application that this tract will address is the late Peter Drucker's declared crisis of productivity--his belief being that businesses and other types of organization are largely wasteful in their production. This author will uphold the extent of Drucker's alert (e.g., managers are turning in productivity growth scores lower than before formal mass business education was introduced) and outline how, through two misconceived and underexploited processes of KM, employers can learn to work more efficiently. The processes are the better management of their organizational memory (OM) and employer-instigated experiential learning, which together can reduce the pandemic of repeated mistakes, reinvented wheels, and other unlearned lessons that litter many parts of modern industry and commerce. All aided by the perceived champion of the workplace--the flexible labor market--which has introduced to industry and commerce the phenomenon of conveyor-belt job discontinuity and associated corporate amnesia, the two most corrosive components to good decision making. Addressing the limitations of conventional approaches, this book takes KM to the next level.